ELOVL2 mediated stabilization of AR contributes to enzalutamide resistance in prostate cancer - Cen, Jinpeng; Guo, Jiading; Zeng, Xianzi; Song, Xianlu; Ge, Shengdong; Chen, Mingkun; Li, Qianyi; Yu, Yuzhong; Lv, Daojun; Zhao, Shanchao (Frontiers in Cell and Developmental Biology, 2025)
IntroductionTo investigate the molecular mechanisms underlying enzalutamide resistance in castration-resistant prostate cancer (CRPC) and explore potential therapeutic strategies to overcome resistance.MethodsWe conducted comprehensive bioinformatic analysis using LNCaP/enzalutamide-resistant cells to identify key pathways associated with resistance. Functional validation was performed through targeted inhibition of the elongation of very-long chain fatty acid protein 2 (ELOVL2), followed by assays to assess cancer cell proliferation and enzalutamide sensitivity. Mechanistic studies were conducted to evaluate the impact of ELOVL2 on the ubiquitin-proteasome system and AR signaling pathways.ResultsBioinformatic analysis revealed that activation of fatty acid metabolism, particularly through upregulation of ELOVL2, plays a critical role in driving enzalutamide resistance in PCa. Functional studies demonstrated that targeted inhibition of ELOVL2 significantly suppressed cancer cell proliferation and restored enzalutamide sensitivity in resistant cells. Mechanistically, ELOVL2 facilitates enzalutamide resistance by impairing the ubiquitin-proteasome system, leading to the subsequent activation of AR signaling pathways.DiscussionOur findings demonstrate that ELOVL2 drives enzalutamide resistance in CRPC by stabilizing AR through inhibition of ubiquitin-proteasome-mediated degradation. Targeting ELOVL2 represents a promising therapeutic strategy to overcome resistance in CRPC, with potential to improve clinical outcomes for patients.